IMPLEMENTASI KETENTUAN HAK ASASI MANUSIA OLEH PRAJURIT POLISI MILITER ANGKATAN UDARA DALAM MENDUKUNG PELAKSANAAN TUGAS OPERASI MILITER - Nyamantoro, Jarot; Sudarto (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2024)
The implementation of the duties of the Air Force Military Police in the activities of criminal investigation and physical security functions, enforcement of discipline and order, investigations and examinations must be guided by the provisions and rules of law and human rights applicable in Indonesia. Therefore, it is very interesting and important to study further how to improve the understanding of Air Force Military Police Soldiers about human rights? and how is the implementation of human rights by Air Force Military Police Soldiers in carrying out operational duties? To answer these problems, a normative legal research method is used with a statutory and conceptual regulatory approach method. Data obtained from primary, secondary, and tertiary legal sources are collected and then analyzed using qualitative data analysis techniques. From the results of the study, it was found that soldiers' understanding of the regulations applicable in the operational area needs to be prioritized, so that internal improvements to the Indonesian National Army in the reform era can help improve the image of the Indonesian National Army as a people's army that in carrying out its duties continues to uphold the law and human rights. The understanding of Air Force Military Police Soldiers regarding human rights in its application must be adjusted to the operational patterns carried out by the Indonesian National Army Air Force in order to improve the understanding of Air Force Military Police soldiers regarding human rights, so in pouring out the optimization of the understanding of Air Force Military Police soldiers regarding human rights in carrying out operational tasks is limited to the main ideas which are the understanding applied to each condition.